2012
DOI: 10.1016/j.hrthm.2012.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac acoustic radiation force impulse imaging: A novel imaging method for intraprocedural evaluation of radiofrequency ablation lesions

Abstract: Background Arrhythmia recurrence after cardiac radiofrequency ablation (RFA) for atrial fibrillation (AF) has been linked to conduction through discontinuous lesion lines. Intraprocedural visualization and corrective ablation of lesion line discontinuities could decrease post-procedure AF recurrence. Intracardiac acoustic radiation force impulse (ARFI) imaging is a new imaging technique that visualizes RFA lesions by mapping the relative elasticity contrast between compliant-unablated and stiff-RFA treated myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 22 publications
1
49
0
Order By: Relevance
“…72 Furthermore, ARFI imaging can distinguish between an incomplete atrial ablation line with a gap and a complete ablation line. 70 The presence of a lesion in the ARFI image is predictive of a conduction disturbance at that location (positive predictive value=96.4% and negative predictive value=90.0%), and the finding of a gap in the ablation line by ARFI imaging predicts lack of conduction block (negative predictive value=71.2%). Finally, ARFI imaging has been successfully adapted to clinical ultrasound and mapping systems during routine clinical catheter ablation procedures with demonstrated feasibility of acquiring ARFI images of radiofrequency lesions from clinically by guest on May 12, 2018 http://circep.ahajournals.org/ Downloaded from relevant ablation target regions in both the right and the left atria ( Figure 4).…”
Section: Acoustic Radiation Force Impulse Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…72 Furthermore, ARFI imaging can distinguish between an incomplete atrial ablation line with a gap and a complete ablation line. 70 The presence of a lesion in the ARFI image is predictive of a conduction disturbance at that location (positive predictive value=96.4% and negative predictive value=90.0%), and the finding of a gap in the ablation line by ARFI imaging predicts lack of conduction block (negative predictive value=71.2%). Finally, ARFI imaging has been successfully adapted to clinical ultrasound and mapping systems during routine clinical catheter ablation procedures with demonstrated feasibility of acquiring ARFI images of radiofrequency lesions from clinically by guest on May 12, 2018 http://circep.ahajournals.org/ Downloaded from relevant ablation target regions in both the right and the left atria ( Figure 4).…”
Section: Acoustic Radiation Force Impulse Imagingmentioning
confidence: 99%
“…69 This method has recently been adapted to an integrated intracardiac mapping and ultrasound imaging system. 70 An ARFI image is created by delivering a series of ultrasound pulses to mechanically displace tissue, measuring the displacement of each image pixel in response to the push pulse using standard ultrasound techniques, and then displaying high-resolution displacement information superimposed on the ultrasound image. Regions of tissue within the imaged field that are stiff demonstrate smaller displacements than more elastic tissue.…”
Section: Acoustic Radiation Force Impulse Imagingmentioning
confidence: 99%
“…puncture to access the LA from the right atrium (RA), visualise the pulmonary vein ostia, visualise the oesophagus to avoid collateral damage, and helps to recognise complications such as perforations. ICE with acoustic radiation force imaging 3 can assess tissue elasticity and directly visualise ablation lesions, which are stiffer than normal portions of the LA, and can potentially identify gaps.…”
Section: Guidancementioning
confidence: 99%
“…Several attempts have been made to provide additional information on functional and morphological RF-induced changes [11][12][13][14][15][16] . Photoacoustic imaging has been used in vitro with encouraging results 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is limited by spatial resolution and the need of MRI-compatible equipment 15 . Optical coherence tomography (OCT) is limited by depth resolution 16 , and acoustic radiation-force impluse (ARFI) is still limited in vivo by motion artifacts 12 . One study used a laboratory-made M-mode catheter 11 , and we found no report of the use of clinically available catheters and twodimensional (2D) echographic imaging.…”
Section: Introductionmentioning
confidence: 99%